SOCIO ECONOMIC DETERMINANTS OF POLITICAL PARTICIPATION AMONG MUSLIM WOMEN IN ASSAM'S CHAR REGIONS - Islam, Irfanul (International Journal of Cultural and Social Science, 2025)
This research investigates the socioeconomic determinants of political participation among Muslim women in the Char regions of Assam, India. Despite constituting a significant portion of the population in these marginalized areas, Muslim women's engagement in political processes remains limited. Through a mixed-methods approach, including surveys, interviews, and focus group discussions, this study explores the influence of factors such as education, economic status, cultural norms, and access to resources on women's political participation. The findings reveal the complex interplay of socioeconomic factors and gender dynamics shaping women's engagement in political activities. The research contributes to a deeper understanding of the barriers faced by Muslim women in political participation and offers insights for promoting inclusive governance and empowerment within marginalized communities.